PHILOSOPHICAL FOUNDATIONS OF SOCIAL JUSTICE AND LEGAL EQUALITY IN THE FORMATION OF A DEMOCRATIC RULE-OF-LAW STATE - Rustamov Sanjar Suyunovich (Bright Mind Publishing, 2026)
This article analyzes the philosophical essence of the principles of social justice and legal equality in the process of forming a democratic rule-of-law state, their historical genesis, and their role in the development of modern society. The study interprets the concepts of justice and equality not only as legal categories, but also as complex philosophical phenomena closely connected with social consciousness, moral values, and political culture. Furthermore, the role of these principles in democratic governance, civil society, and the protection of human rights is examined.
Keywords: Democratic state, rule-of-law state, social justice, legal equality, human rights, rule of law, civil society, philosophical foundations.